Plataformas diagnósticas para a análise de processos alérgicos e contaminantes alergênicos derivados dos ácaros Blomia tropicalis e Dermatophagoides sp - Alves, Claudiney de Freitas (2018)
The Allergic diseases represent a major public health problem and are common in the general population. These diseases have increased considerably over the last decades. Today, allergies, mediated as "evil of the century," represent the fourth group of chronic diseases with high prevalence and rapid global growth. These affect about 35-40% of the population and are considered epidemics of modern civilization. This exponential increase is mainly due to changes in habits of modern life (Hygiene Theory) and to environmental pollution. The allergy consists of an exaggerated response of the immune system, when the genetically predisposed individual (atopic), is exposed to the presence of some allergen. These stimuli (allergens) can be the presence of dust, smoke, some drug component, strong smells, insect bites, in ingestion of certain foods, among others that are capable of provoking an exacerbated reaction of the immune system. This reaction results in the production of high levels of immunoglobulin E (IgE) with low doses of allergenic stimuli that can be life threatening to the wearer, as it can lead to anaphylactic shock. The Allergies are type I hypersensitivity reactions and reach in their heterogeneity different organs and systems, such as skin, respiratory and digestive tracts, as mentioned in the previous examples. These reactions negatively affect the quality of life of individuals. In domestic and storage environments, the mites are the main cause of these reactions. Mites are microscopic animals belonging to a subclass of arachnids. Storage mites are found mainly in stored foods, cereals, flours, barns and hay. However, these mites can also be found in house dust and therefore exposure to these animals can also occur at home, especially in humid places. The mites most studied are of the genus Dermatophagoides and Blomia, since they have clinically relevant allergens for the development of allergies. The difficulties in diagnosis and appropriate treatment are a reality when it comes to allergic diseases and represent an increased difficulty for the quality of life of individuals. Such diagnosis may be made by skin testing or by measuring serum levels of specific IgE. However, these methods are expensive and time-consuming to indicate the result of a sample. In this way, the development of new methods of prevention, detection, diagnosis and treatment for allergic diseases are necessary. Raman spectroscopy is a promising technique for biomedical applications since it does not exhibit water signals in its result. This is a fast and non-destructive vibrational spectroscopy technique in which a laser is focused on a sample. The technique is based on the interaction of the incident photons with the molecules of the sample generating an inelastic scattering of photons with frequencies and intensities characteristic of the molecules in the sample. The resulting Raman spectrum provides a fingerprint characteristic of molecular composition which can identify the species in the sample. In addition to precise and rapid diagnostic techniques, the control of allergic manifestations is based on the reduction to allergenic exposure. The development of electrochemical (immuno) biosensors arouses the attention of the scientific community because these devices, associated to the selectivity of the electrochemical measurements, have allowed the measurement of several important analytes in different areas such as medical, pharmaceutical, food and environmental. The demand for the development of simple, fast, accurate, sensitive, specific, selective, low cost and portable analytical instruments is growing and the (immuno) biosensors meet these requirements. This thesis aims to identify specific patterns for each type of antigen using monoclonal antibodies, serum (Raman) and polyclonal antibodies (biosensor) that aim to improve the ways of diagnosis and identification of possible means of exposure, with consequent improvement of the treatment of these diseases. Indicated whether the individual is atopic or non - atopic in addition to possible sources of contamination with the mite antigens of Blomia tropicalis. For a better understanding of this work, this thesis was divided into chapters. Chapter 1 refers to the theoretical basis of the thesis. In this chapter, the main milestones related to the development of allergic diseases are described. This chapter also provides a brief review of the epidemiology of the disease, a presentation of its risk factors, and mentions some methods used to diagnose these diseases. Chapter 2 investigates the use of the Raman technique to determine whether the individual is allergic (atopic) or not. Therefore, the objective of this chapter is to investigate the serum of different patients in search of evidence that frames them in patients or not, analyzing the spectra obtained with the Raman technique. Finally, Chapter 3 investigates the use of electrochemical immunoassays as a future alternative for the identification of samples contaminated with dust mite allergens. Therefore, the purpose of this chapter is to present in more detail the use of modified electrochemical immunosensors with polyclonal immunoglobulin Y for Blomia tropicalis - Blot 5 detection.